Bimetallic M/N/C catalysts prepared from π-expanded metal salen precursors toward an efficient oxygen reduction reaction. Issue 6 (12th January 2018) - Onoda, Akira; Tanaka, Yuta; Matsumoto, Koki; Ito, Minoru; Sakata, Takao; Yasuda, Hidehiro; Hayashi, Takashi
Abstract : Bimetallic metal and nitrogen-containing carbon (M/N/C) catalysts were prepared by pyrolysis of a mixture of carbon support and π-expanded Fe(salen) and Cu(salen) precursors. The bimetallic catalyst promotes efficient four-electron reduction of dioxygen. Abstract : Nonprecious metal electrocatalysts are being explored as alternatives to platinum-group metal electrocatalysts for the oxygen reduction reaction (ORR) which is required for cathode materials in fuel cells. Herein, we describe a new method for preparing bimetallic nitrogen-containing carbon catalysts with high ORR activity using π-expanded M(salen) precursors. The M/N/C and bimetallic FeM/N/C ORR catalysts were obtained by pyrolysis of a mixture of a carbon support (Vulcan XC-72R) and the metal complex as a precursor. The bimetallic FeCu catalyst prepared from Fe and Cu complexes with the N, N ′-bis(2-hydroxy-1-naphthylidene)-1, 2-phenylenediamine ligand (2NAPD) is found to have an onset potential of 0.87 V, which is positively shifted by 50 mV from that of the catalyst prepared from the monometallic Fe(2NAPD) complex. The FeCu/N/C catalyst promotes efficient four-electron reduction in the ORR. High-resolution transmission electron microscopy studies reveal that both Fe and Cu metals together with pyridinic nitrogen species are highly dispersed within the carbonaceous structure in FeCu/2NAPD@VC, suggesting that the N-coordinated Fe and Cu sites promote efficient four-electron reduction of O2 . This new methodology facilitates design of nonprecious bimetallic carbon catalysts with excellent ORR activity.